Influencia de la aplicación de dos tipos de levaduras y el tiempo de fermentación en la calidad organoléptica de Coffea arabica var. Sidra de la finca Agroloja - Alvarez Barco, Santiago Miguel (2023)
This research aimed to evaluate the application influence of two types of yeast and the fermentation time on the organoleptic quality of Coffea arabica var. Sidra from Agroloja farm, for that, an experimental design was developed through five treatments with five replicates for each one, which were composed of a representative sample of 1,1 kg of C. arabica var. Sidra in which the Saccharomyces cerevisiae S-04 and WB- 06 strains were evaluated, as well as a fermentation time limit of four and six days with a wet milling process and an optimal drying time, to finally work with tasting tests that were carried out following the SCAA standards for threshing, selection of defects, grinding, roasting and tasting by skilled professionals. Obtained results show that both the pH and Brix degrees tend to decrease with the passage of days of fermentation, while the highest tasting score and the special notes found, describe that the treatment with the S-04 strain is the most effective, since it got the best scores regardless of fermentation time, however, treatment four had better attributes in fragrance/smell, acidity and body, unlike treatment two, which presented better attributes in flavor, aftertaste and balance, although the numerical differences between the organoleptic characteristics of second and fourth treatments are minimal, compared to the other treatments, they are very relevant, mainly because of the final score obtained. Therefore, treatments used have an influence on the fermentation processes and the final cup quality, especially regarding generating descriptors and special notes in cupping. Keywords: Coffee, yeast, fermentation, pH, Brix degrees, cup quality.